PENGARUH KARAKTERISTIK SISTEM INFORMASI MANAJEMEN DAN SOP TERHADAP KINERJA MANAJERIAL (Studi Kasus Pada Citarum Sobat Bumi) - Iseu Anggraeni (Fakultas Ekonomi UNIBBA, 2016)
This research is an case study that aims to test the hypotheses related to the influence of the variable characteristics of management in formation systems and standard operating procedures (SOP) on the performance of managerial Citarum Sobat Bumi (CSB). This research used a qualitative approach with survey design. Respondents were senior managers and staff with 42 sampleof the total population. Data analysis technique to test the hypothesis is the path analysis. The results showed there were significant and simultaneously effects the characteristics of managementinformation systems and standard operating procedure (SOP) on managerial performance in Citarum Sobat Bumi is equal to 49.6%, and the remaining 50,4% is influenced by other factors not examined by the authors factors such as organizational climate, leadership, satisfaction, compensation and others.